PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS POP-UP PADA MATERI PERUBAHAN WUJUD BENDA PEMBELAJARAN IPAS KELAS IV - arum, wijayanti; Sudirman; Mansur Hakim; Nurwahidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This research is motivated by observations conducted at SDN 1 Taman Ayu, which revealed that the learning process still lacks the use of instructional media, particularly in delivering the topic of changes in the states of matter. The learning process remains heavily reliant on textbooks as the sole learning source, which negatively affects students’ understanding of the material. To address this issue, the researcher developed an instructional medium in the form of pop-up-based flashcards designed to attract students' interest in learning while also facilitating their conceptual understanding of the topic. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included interviews and questionnaires. Data analysis was conducted through feasibility validation by media and content experts, as well as feedback from teachers and students regarding the developed media. The validation results indicated that the pop-up-based flashcard media achieved a very high level of feasibility, with feasibility percentages of 96% from the media expert, 82.5% from the content expert, and 98% from the teacher's response. Furthermore, students gave positive responses to the use of this media in the learning process. Based on these findings, it can be concluded that the pop-up-based flashcard media is highly feasible for use as a learning tool in teaching the topic of changes in the states of matter in fourth-grade elementary school. This study recommends the development of similar media for other topics to support learning variation in elementary schools.